2016
DOI: 10.1002/gj.2807
|View full text |Cite
|
Sign up to set email alerts
|

Origin of transform faults in back‐arc basins: examples from Western Pacific marginal seas

Abstract: Transform faults in back‐arc basins are the key to revealing the evolution of marginal seas. Four marginal basins in the Western Pacific, i.e. the South China Sea (SCS), Okinawa Trough (OT), West Philippine Basin (WPB) and Shikoku‐Parece Vela Basin (SPVB), were studied to redefine the strikes and spatial distribution of transform faults or fracture zones. Based on high‐resolution tectonomorphology, gravity and magnetic anomalies, pattern of magnetic lineations, seismic profiles, geometry of basins and palaeoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 99 publications
(215 reference statements)
0
14
0
Order By: Relevance
“…The third boundary conditions may be more consistent with the real Mesozoic evolution of the ECSCSB (Figure 7). Li, Yu, et al (2013) and Zhang et al (2016) Plate. Thus, we think that the extension of the basin has relationship with the subduction retreat of the Izanagi Plate on the two-dimensional model, and extension is one of the factors for evolution of the basin.…”
Section: Comparison Of Simulation Results and Balanced Sectionsmentioning
confidence: 98%
See 2 more Smart Citations
“…The third boundary conditions may be more consistent with the real Mesozoic evolution of the ECSCSB (Figure 7). Li, Yu, et al (2013) and Zhang et al (2016) Plate. Thus, we think that the extension of the basin has relationship with the subduction retreat of the Izanagi Plate on the two-dimensional model, and extension is one of the factors for evolution of the basin.…”
Section: Comparison Of Simulation Results and Balanced Sectionsmentioning
confidence: 98%
“…Li, Yu, et al () and Zhang et al () analysed the temporal and spatial distribution of magmatic rocks around 160 Ma in East China. It was found that the Andean‐type continental margin developed a large number of plutons, such as Dandong, Guojialing, and South China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that the cross-arc chains follow long-lived basement structures, inherited from or even pre-dating successive back-arc opening episodes [Fryer and Hussong, 1982;Fryer, 1995]. Zhang et al [2016] considered that transform faults in the South China Sea, Okinawa Trough, West Philippine Basin, and Shikoku-Parece Vela basins are similarly inherited structures, the highly oblique orientation of which reflects complex plate convergence and rotation. Thus, the segmentation of the Mariana back-arc spreading center may be controlled by an early fabric in the arc crust, with all of the major and minor offsets associated with a major E-W or NE-SW trending structures at the regional scale (Figure 15b).…”
Section: Regional Structuresmentioning
confidence: 91%
“…However, the NSCSM had been convergent through the Mesozoic era under multi‐source stress fields due to closures of the Tethys and Paleo‐Pacific oceans among the Indo‐Australian, Eurasian, and Paleo‐Pacific plates. The NE‐trending dextral strike‐slip faults inherited and propagated from the Late Mesozoic faults with the same strike direction in South China, which mainly consist of a series of horse‐tail‐like secondary splay faults in plan view (Hui et al, , ; Li et al, ; Wang et al, ; Zhang et al, ). The Meso‐Cenozoic basins in the northern SCS continental margin are partially exposed to reveal a chessboard pattern in a NE‐oriented distribution due to the NE‐trending dextral strike‐slip faulting which dominate over the E–W‐ and NW‐trending faults (Li et al, ; Figure ).…”
Section: Geological Settingmentioning
confidence: 99%